Tearing of clothes A study of an ancient practice in the Old Testament - Obiorah, Mary Jerome; Uroko, Favour C. (2018)
Tearing of clothes occurs in sorrowful occasions but there is a class of person that the law excludes from this custom. This article attempts a synopsis and a synchronised presentation of all the occurrences of this phenomenon in the Old Testament. Particular attention is paid to the verbal roots and mood employed for the action of rending clothes, words used for clothes, persons performing the action, reasons for the action and contexts. The specific objective of the study is to elucidate this ancient practice, especially the contexts in which it is found in the Old Testament.Intradisciplinary and/or interdisciplinary implications: The research on ancient Israel's practice of tearing clothes is a biblical analysis of this phenomenon in the Old Testament. It is discovered that this practice was used as an external manifestation of personal or communal dolorous experience, still practised among Jews today. Disciplines implicated are sociology and psychology.
Keywords: Ancient Israel; ancient oractice; Old Testament; tearing of clothes